The Influence of Recombinational Processes to Induce Dormancy in Trypanosoma cruzi - Resende, Bruno Carvalho; Oliveira, Anny Carolline Silva; Guañabens, Anna Carolina Paganini; Repolês, Bruno Marçal; Santana, Verônica; Hiraiwa, Priscila Mazzochi; Pena, Sérgio Danilo Junho; Franco, Glória Regina; Macedo, Andrea Mara; Tahara, Erich Birelli; Fragoso, Stênio Perdigão; Andrade, Luciana Oliveira; et al. (Frontiers in Cellular and Infection Microbiology, 2020)
The protozoan Trypanosoma cruzi is the causative agent of Chagas disease, a neglected tropical disease that affects around 8 million people worldwide. Chagas disease can be divided into two stages: an acute stage with high parasitemia followed by a low parasitemia chronic stage. Recently, the importance of dormancy concerning drug resistance in T. cruzi amastigotes has been shown. Here, we quantify the percentage of dormant parasites from different T. cruzi DTUs during their replicative epimastigote and amastigote stages. For this study, cells of T. cruzi CL Brener (DTU TcVI); Bug (DTU TcV); Y (DTU TcII); and Dm28c (DTU TcI) were used. In order to determine the proliferation rate and percentage of dormancy in epimastigotes, fluorescent-labelled cells were collected every 24 h for flow cytometer analysis, and cells showing maximum fluorescence after 144 h of growth were considered dormant. For the quantification of dormant amastigotes, fluorescent-labelled trypomastigotes were used for infection of LLC-MK2 cells. The number of amastigotes per infected LLC-MK2 cell was determined, and those parasites that presented fluorescent staining after 96 h of infection were considered dormant. A higher number of dormant cells was observed in hybrid strains when compared to non-hybrid strains for both epimastigote and amastigote forms. In order to investigate the involvement of homologous recombination in the determination of dormancy in T. cruzi, we treated CL Brener cells with gamma radiation, which generates DNA lesions repaired by this process. Interestingly, the dormancy percentage was increased in gamma-irradiated cells. Since we have previously shown that naturally-occurring hybrid T. cruzi strains present higher transcription of RAD51 – a key gene in recombination process –, we also measured the percentage of dormant cells from T cruzi clone CL Brener harboring single knockout for RAD51. Our results showed a significative reduction of dormant cells in this T cruzi CL Brener RAD51 mutant, evidencing a role of homologous recombination in the process of dormancy in this parasite. Altogether, our data suggest the existence of an adaptive difference between T. cruzi strains to generate dormant cells, and that homologous recombination may be important for dormancy in this parasite.